2007
DOI: 10.1177/0040517507078023
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Influence of Knit Structure and Stitch Length on Ring and Compact Yarn Single Jersey Fabric Properties

Abstract: This study focused on the effect of single jersey, single pique, double pique and honeycomb structures and structural cell stitch length (SCSL) on ring and compact yarn single jersey fabric properties. Compact yarn fabrics showed better performance in all the structures and their respective SCSL. With increased SCSL, the dimensional properties like CPI, WPI, SD, grams per square meter, thickness and tightness factor decreased for all the structures, while comfort properties like air permeability and water abso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 2 publications
(3 reference statements)
4
58
0
4
Order By: Relevance
“…Several research studies have been conducted in the past concerning performance, moisture management and thermal comfort aspects of knitted fabrics [8][9][10][11]. Kane et al [12] studied the effect of fabric density on water absorption properties of fabrics. They observed that double pique fabric, which has greater density than single jersey fabrics, shows better water drop absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Several research studies have been conducted in the past concerning performance, moisture management and thermal comfort aspects of knitted fabrics [8][9][10][11]. Kane et al [12] studied the effect of fabric density on water absorption properties of fabrics. They observed that double pique fabric, which has greater density than single jersey fabrics, shows better water drop absorption.…”
Section: Introductionmentioning
confidence: 99%
“…This appears to confirm the report of pique fabrics producing lower prickle responses during fabric wearer trials where other aspects of fabric design and construction and WCM The Journal of The Textile Institute 603 assessment were also accounted for in prediction models (McGregor et al, in press). While the same yarn is used for both pique and single jersey fabrics, the pique fabric is thicker, more stable to treatments and changes in CF and has a more open surface structure (Kane, Patil, & Sudhakar, 2007) (Figure 2). Accordingly, more protruding fibres sit deep in the surface of the pique fabric compared with single jersey fabrics.…”
Section: Resultsmentioning
confidence: 99%
“…Geçmişte gerçekleştirilen çalışmalar boncuklanma seviyesinin lif özellikleri (lif tipi, lif inceliği vb) [6][7][8][9][10], iplik parametreleri (iplik numarası, büküm katsayısı, tüylülük, sürtünme katsayısı, üretim yöntemi vb) [3,[11][12][13], kumaş yapısal özellikleri (üretim yöntemi, konstrüksiyon) [14,15] ve kumaşa uygulanan bitim işlemleri [16][17][18] gibi çeşitli faktörlere bağlı olduğunu göstermektedir. Kumaş oluşumundan sonra boncuklanmanın giderilmesi için yakma ve makaslama gibi mekanik işlemlerin yanı sıra çeşitli kimyasal ve biyolojik işlemler de uygulanmaktadır.…”
Section: Gġrġġunclassified